Composite 3D printed scaffold with structured electrospun nanofibers promotes chondrocyte adhesion and infiltration. Issue 3 (4th May 2018) - Rampichová, M.; Košt'áková Kuželová, E.; Filová, E.; Chvojka, J.; Šafka, J.; Pelcl, M.; Daňková, J.; Prosecká, E.; Buzgo, M.; Plencner, M.; Lukáš, D.; Amler, E.
ABSTRACT: Additive manufacturing, also called 3D printing, is an effective method for preparing scaffolds with defined structure and porosity. The disadvantage of the technique is the excessive smoothness of the printed fibers, which does not support cell adhesion. In the present study, a 3D printed scaffold was combined with electrospun classic or structured nanofibers to promote cell adhesion. Structured nanofibers were used to improve the infiltration of cells into the scaffold. Electrospun layers were connected to 3D printed fibers by gluing, thus enabling the fabrication of scaffolds with unlimited thickness. The composite 3D printed/nanofibrous scaffolds were seeded with primary chondrocytes and tested in vitro for cell adhesion, proliferation and differentiation. The experiment showed excellent cell infiltration, viability, and good cell proliferation. On the other hand, partial chondrocyte dedifferentiation was shown. Other materials supporting chondrogenic differentiation will be investigated in future studies.